2017
DOI: 10.2306/scienceasia1513-1874.2017.43.096
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic, cytotoxic, and antibacterial activities of essential oil isolated from Citrus hystrix

Abstract: ABSTRACT:The essential oil obtained from the peel of Citrus hystrix fruits is a colourless or light yellow liquid with a strong citrus scent. It was analysed for its constituents using gas chromatography/mass spectroscopy. The major components of the oil were β-pinene, limonene, terpinen-4-ol, α-pinene, α-terpinene, γ-terpinene, and α-terpineol. The antibacterial activity of C. hystrix essential oil was tested by disc diffusion and serial macrodilution methods against 50 multidrug-resistant Acinetobacter bauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Prominent antibacterial effects have been stated to the C. hystrix essential oil, assessed by disc diffusion and serial macro dilution methods against 50 multidrug-resistant Acinetobacter baumannii strains. The results revealed a good activity against the tested strains, expressed by minimal inhibitory concentrations (MICs) ranging from 0.125 to 1 µl/mL [38]. Srisukh et al [39] investigated the effect of the individual compounds present in C. hystrix leaves and fruit [38].…”
Section: Kaffir Lime and Other Citrus Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prominent antibacterial effects have been stated to the C. hystrix essential oil, assessed by disc diffusion and serial macro dilution methods against 50 multidrug-resistant Acinetobacter baumannii strains. The results revealed a good activity against the tested strains, expressed by minimal inhibitory concentrations (MICs) ranging from 0.125 to 1 µl/mL [38]. Srisukh et al [39] investigated the effect of the individual compounds present in C. hystrix leaves and fruit [38].…”
Section: Kaffir Lime and Other Citrus Fruitsmentioning
confidence: 99%
“…The results revealed a good activity against the tested strains, expressed by minimal inhibitory concentrations (MICs) ranging from 0.125 to 1 µl/mL [38]. Srisukh et al [39] investigated the effect of the individual compounds present in C. hystrix leaves and fruit [38]. On the other side, Citrus sinensis (sweet orange) peel extract notably prevented liver injury through lowering the levels of both TNF-α and INF-γ as well as of regulatory T (reg-T) cells, while increased the IL-10 levels [41].…”
Section: Kaffir Lime and Other Citrus Fruitsmentioning
confidence: 99%
“…As the compounds in the kaffir lime oil are highly lipophilic, it can readily pass through the lipid component of bacterial cell membrane causing alteration in structure integrity rendering them permeable. This leads to leakage of cell contents and ions, lowering the membrane potential of the cell that disrupts the proton pump and eventually causes death 70‐72 . It was also reported that the cell death can be caused by coagulation of cytoplasm which stops the metabolism and renders death 72 …”
Section: Application Of Kaffir Lime Oilmentioning
confidence: 99%
“…Các loại tinh dầu cây có múi cũng rất giàu các hợp chất hoạt tính sinh học, được công nhận cho các giá trị dược phẩm, sinh lí và dược lí. Như đã được chứng minh bởi nhiều nghiên cứu, tinh dầu cam quýt có đặc tính chống vi khuẩn, chống nhiễm trùng, kháng khuẩn, chống oxi hóa, chống ung thư, chống nấm, chống viêm và hạ đường huyết [7][8][9]. Tinh dầu chứa các chất dễ bay hơi được phân lập thông qua các phương pháp chiết xuất từ thực vật của một loài thực vật duy nhất.…”
Section: Từ Khóa Mahd Gc-ms 1 Giới Thiệuunclassified